Influence of different milk-clotting enzymes on the process of producing semihard cheeses - D. S. Myagkonosov; I. T. Smykov; D. V. Abramov; I. N. Delitskaya; E. G. Ovchinnikova (Пищевые системы, 2023)
The effect of milk-clotting enzymes (MCEs) of animal origin (Naturen Extra with a mass fraction of chymosins of 95%, “Bovine Pepsin” with a mass fraction of chymosin of 10%), as well as MCEs of microbial origin (Fromase 750 XLG) and recombinant origin (Chy-max Extra and Chy-max Supreme) on the duration of milk coagulation and processing of cheese curd, as well as on the composition of whey and fresh cheeses in the manufacture of semihard cheeses, at an introduction dose of MCE of 1,500 to 6,000 IMCU per 100 kg of milk. Increasing the MCE dose from 1,500 to 2,000–3,000 IMCU/100 kg of milk leads to a decrease in the coagulation duration by an average of 20 min (p<0.05). A further increase in the MCE dose to 5,000–6,000 IMCU/100 kg of milk does not lead to a reduction in the coagulation duration. With equal introduction doses, MCE brands of Fromase and “Pepsin” show greater losses of fat (by 0.15–0.60%) and dry matter (by 0.30–0.50%) in whey than MCEs of Naturen brands, Chymax Extra and Chy-max Supreme. Cheese variants made using different types and doses of MCEs did not have statistically accurate differences in the content of dry matter, fat, protein, salt and pH (p>0.05). The use of MCEs of Naturen, Chy-max Extra and Chy-max Supreme brands at a dosage of 5,000–6,000 IMCU/100 kg of milk gives an average of 1.5% higher actual cheese yield compared to MCEs of the Fromase and “Pepsin” brands at an introduction dose of 1500 IMCU/100 kg of milk.